Assessing the Current State of Amber Force Field Modifications for DNA─2023 Edition - Love, Olivia; Galindo-Murillo, Rodrigo; Zgarbová, Marie; Šponer, Jiří; Jurečka, Petr; Cheatham, Thomas E (Journal of chemical theory and computation, 2023)
Advances in molecular dynamics (MD) software alongside enhanced computational power and hardware have allowed for MD simulations to significantly expand our knowledge of biomolecular structure, dynamics, and interactions. Furthermore, it has allowed for the extension of conformational sampling times from nanoseconds to the microsecond level and beyond. This has not only made convergence of conformational ensembles through comprehensive sampling possible but consequently exposed deficiencies and allowed the community to overcome limitations in the available force fields. The reproducibility and accuracy of the force fields are imperative in order to produce biologically relevant data. The Amber nucleic acid force fields have been used widely since the mid-1980s, and improvement of these force fields has been a community effort with several artifacts revealed, corrected, and reevaluated by various research groups. Here, we focus on the Amber force fields for use with double-stranded DNA and present the assessment of two recently developed force field parameter sets (OL21 and Tumuc1). Extensive MD simulations were performed with six test systems and two different water models. We observe the improvement of OL21 and Tumuc1 compared to previous generations of the Amber DNA force. We did not detect any significant improvement in the performance of Tumuc1 compared to OL21 despite the reparameterization of bonded force field terms in the former; however, we did note discrepancies in Tumuc1 when modeling Z-DNA sequences.
Keywords: simulace molekulární dynamiky; Reproducibility of Results; Molecular Conformation; Z-DNA; Molecular Dynamics Simulation; reprodukovatelnost výsledků; molekulární konformace; DNA; DNA, Z-Form